The Importance of Originality in Scientific Research on Neglected Tropical Diseases Cannot Be Overstated: Through Our Original Ideas and Investigations, We Can Hope to Make Significant Strides in Understanding and Combating these Diseases - Teixeira, Antonio R. L. (Advances in Social Sciences Research Journal, 2024)
The pace of scientific research on neglected tropical diseases, such as Malaria, Leishmaniases, African trypanosomiasis, and Chagas disease (American Trypanosomiasis), has been perceived as slow, potentially failing to keep up with the escalating burden on the global human population. While there have been strides in the treatment and partial prevention of some neglected diseases, the alarming global spread of Leishmaniases and Chagas disease is a cause for concern. To contribute to the discourse on these neglected tropical diseases, examining the morbidity and mortality rates, which have now become a pressing global health issue necessitating international solidarity, is crucial.